Effect of gender-affirming treatments on depression and anxiety symptoms in transgender people: a retrospective cohort study - Wong, Chun Yip; Ngan, Sze Ting Joanna; Cheng, Pak Wing Calvin; Tang, Wing Ki; Chow, Lai Yin; Kam, Wai Kwok (Frontiers in Psychiatry, 2026)
IntroductionGiven the unique mental health challenges among transgender individuals, it is imperative to understand the effectiveness of gender-affirming treatments in alleviating psychological distress. The existing literature gap calls for studies with larger sample sizes, extended follow-up periods, and rigorous controls for confounding variables. This study aims to explore if gender-affirming surgery (GAS) and gender-affirming hormone therapy (GAHT) is associated with improvement in symptoms of depression, anxiety, and gender incongruence among transgender individuals attending a specialist clinic in Hong Kong.MethodsIn this retrospective cohort which consisted of 394 treatment-seeking transgender participants at baseline, 178 individuals were recruited from October 2023 to June 2024 and completed self-rated questionnaires to assess depressive and anxiety symptoms and gender incongruence. Socio-clinical profiles and questionnaire scores were compared among treatment status groups. Longitudinal changes in mental health outcome scores were analyzed using linear mixed-effects regression models, incorporating time-by-group interactions and random intercepts to account for individual baseline differences.ResultsGender-affirming treatments did not reduce depressive or anxiety symptoms significantly, after controlling for coping and social support. However, both GAS and GAHT were associated with significant improvements in gender congruence over time. Mood symptoms were significantly associated with social support and coping. Various sociodemographic and psychosocial factors, including employment status, living situation, psychological care, and psychiatric medication use, were associated with psychological outcomes.DiscussionGender-affirming medical treatments alone may not entirely resolve the mental health difficulties faced by transgender individuals. Future research needs to better elucidate the impacts of persistent psychosocial challenges such as discrimination and rejection, as well as potential treatment complications. The treatment-seeking nature of this cohort, coupled with baseline psychiatric interventions, may have obscured significant correlations. While gender-affirming treatments can enhance gender congruence, our findings highlight the importance of holistic approaches to strengthen adaptive buffering mechanisms throughout the gender transition process.